Are the Agro-Ecosystems Sustainable? Measurement and Evaluation: A Case Study of Sichuan Province, China - Dai, Xiaowen; Chen, Yi; Wu, Xin; He, Yanqiu; Wang, Fang (Frontiers in Environmental Science, 2022)
The agricultural sustainable development and green developments are important contents and forms of ecological civilization, and they are also important contents of the Carbon-Neutral action in China nowadays. Sichuan province is a large traditional agricultural province. It is an essential national grain production and storage base in western China. Agricultural sustainable development in Sichuan is a significant foundation for the sustained and healthy development of the regional agricultural economy and food security. Our research mainly focuses on the investigation of agricultural sustainable development capacity in Sichuan Province. We use the ecological footprint model to do this research. Our analysis shows that: (1) The cultivated land, forest land, and water area in the overall agricultural ecosystem of Sichuan Province are in an ecological surplus state for the past 20 years. However, during the same period, the grassland ecosystem in Sichuan has been in an ecological deficit state; (2) Forest land is the most sustainable, safest land and has higher resource utilization all the time, following are water land, arable land, and grassland. While in the coordination of ecology and economy, all lands are improving. In general, the overall environmental pressure of Sichuan's overall agricultural ecosystem continues to decrease. However, there is an uneven development within the ecosystem. The sustainability of forest land has increased, water area and cultivated land have declined in the past two decades, and the long-term ecological deficit of the grassland ecosystem needs to be taken seriously.